2019
DOI: 10.1021/acsami.9b12041
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Electrochemical Performance of Sodium Manganese Ferrocyanide by Na3(VOPO4)2F Coating for Sodium-Ion Batteries

Abstract: Sodium manganese ferrocyanide Na x Mn­[Fe­(CN)6] y is an attractive cathode material for sodium-ion batteries. However, Na x Mn­[Fe­(CN)6] y prepared by simple coprecipitation of Mn2+ and [Fe­(CN)6]4– usually shows poor cycling performance, which hinders its practical application. In this work, electrochemical performance of a Na1.6Mn­[Fe­(CN)6]0.9 (PBM) sample prepared by the simple precipitation method was greatly improved by coating with Na3(VOPO4)2F (NVOPF) via a solution precipitation method. The as-pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Some inorganic materials have also been found that could also act as protective layers and conductors to enhance the electrochemical performance of PBA electrodes. For example, MnO 2 , [136] ZnO, [137] 2D MoS 2 , [138] Na 3 (VOPO 4 ) 2 F, [139] etc. have been reported that could form composites with PBAs, resulting in better rate and cycling performance.…”
Section: Surface Modificationmentioning
confidence: 99%
“…Some inorganic materials have also been found that could also act as protective layers and conductors to enhance the electrochemical performance of PBA electrodes. For example, MnO 2 , [136] ZnO, [137] 2D MoS 2 , [138] Na 3 (VOPO 4 ) 2 F, [139] etc. have been reported that could form composites with PBAs, resulting in better rate and cycling performance.…”
Section: Surface Modificationmentioning
confidence: 99%
“…Ma's group reported a surface coating of NaMnHCF using Na 3 (VOP 4 ) 2 F (NVOPF), which is achieved by annealing a chemical precursor at 200 °C (in vacuum) ( Figure 16 a–f). [ 157 ] NVOPF is a well‐known NASICON‐type cathode having excellent rate capability and long‐term cycling stability. [ 160,161 ] Due to the high Na + conductivity and the uniform coating (30 nm) of NVOPF, the interface charge transfer is effectively enhanced, resulting in much better high‐rate performance of the NaMnHCF@NVOPF than the bare one although its low‐rate capacities are lower.…”
Section: Compositing and Surface Modificationmentioning
confidence: 99%
“…Reproduced with permission. [ 157 ] Copyright 2019, American Chemical Society. f) TEM image, g) electrochemical impedance, h) cycling performance, and i) rate performance of PB@PANI in nonaqueous NIBs.…”
Section: Compositing and Surface Modificationmentioning
confidence: 99%
“…NaTMO 2 (TM = Fe, Co, Mn, Ni, Cr, etc. ), polyanion-type materials, and prussian blue analogues, are widely investigated as cathode materials for SIBs. In particular, layered Na x TMO 2 compounds are intensely reported due to their easy synthesis methods and promising electrochemical properties. ,, …”
Section: Introductionmentioning
confidence: 99%